“Who makes the news?”: 25 years of the global media monitoring project: Assessing women’s presence in the media - Martínez Rodríguez , Beatriz (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The GMMP or Global Media Monitoring Project is the largest study on the presence of women in the media in the world. In 6 editions, over the last 25 years, it has longitudinally analyzed how women are represented in the media around the world. In these 25 years, the change in the three elements that affect the study - the media, the situation of women and the monitoring task itself - has been relevant and multifactorial. Is this evolution noticeable in the results obtained in the successive content analyses?